Building Virtual Local Area Network (VLAN) for Self-Attendance Using Manageable Switch at Institut Sains & Teknologi Akprind Yogyakarta - Firmansyah Firmansyah; Bayu Wibisana; Hendri Purnomo; Yusuf Hendra Pratama (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2023)
Building a manageable network to support the implementation of Virtual Local Area Network (VLAN) in independent attendance for students and lecturers, which can avoid individuals entrusting attendance, is part of today's technological developments, so that it is hoped to produce an individual who is independent, intelligent and supported. with a high level of technological mastery. The AKPRIND Yogyakarta Institute of Science & Technology has implemented this technology on the main server, but the VLAN implementation is specifically designed for Presence Mandiri in the west and east buildings on campus 1. Each building is designed to have 2 broadcast domains and use 2 switches to be able to produce communications. data between buildings that have the same broadcast domain. The switch on the Presence Mandiri VLAN network at the AKPRIND Yogyakarta Institute of Science & Technology has 2 VLAN IDs with the configuration used being VLAN Trunking (VTP). The IP addressing provided is DHCP from each switch, which can divide the network on each available port. This VLAN configuration is all done using a network simulation tool, namely Cisco Packet Tracert 6.1.0 in ICMP testing, with the protocol used is Internet Protocol version 4 or IPv4